Design and analysis of a vertical axis wind turbine - Koh, Jian Hao. (2011)
Recently, there has been a resurgence of interest in vertical axis wind turbines (VAWT) due to its advantages over the conventional horizontal axis wind turbines. More experimental and numerical simulations is needed for the understanding of VAWT operations, and the performance for different blade design and turbine configurations needs to be investigated to develop more efficient VAWT designs. In this project, a small scale VAWT was designed and built in which the blade design and configuration could be modified easily for testing. Performance characteristics with SD8020, NACA0022 and S1223 airfoils at different turbine configuration were also analyzed. Finally, a basic flow simulation was performed which illustrated the blockage effect of wind tunnel testing. Experimental test showed that NACA0022 blades which are symmetric and thick gave the best P C performance while the asymmetric S1223 blades also showed promising results when placed in the right configuration. It was also deduced that 4-blade configuration has a better self-starting performance than a 3-blade configuration due to its higher solidity. The CFD simulations suggested that the P C values could be augmented in a wind tunnel test.